Level of homocysteine and polymorphism of genes involved in folate metabolism in women with polycystic ovary syndrome - T.L. Arkhypkina; V.A. Bondarenko; L.P. Lyubimovа; K.V. Misiura (Mìžnarodnij Endokrinologìčnij Žurnal, 2023)
Background. Polycystic ovary syndrome (PCOS) is a multifactorial disease in the development of which gene polymorphism plays an important role. In recent years, data on the role of homocysteine (Hcy) in the formation of PCOS have appeared, and hyperhomocysteinemia is even considered one of the main symptoms of this disease. The causes of an impaired Hcy metabolism are varied and mainly depend on the condition of the genes encoding enzymes of the folate cycle. At the same time, available data on the effect of the 5,10-methylenetetrahydrofolate reductase (MTHFR), methionine synthase (MTR), and methionine synthase reductase (MTRR) gene polymorphisms on the development of hyperhomocysteinemia and the risk of PCOS are few and contradictory. The purpose of the study was to investigate the polymorphisms of the main genes encoding enzymes of the folate cycle (MTHFR, MTR, MTRR) and to reveal their relationship with the level of Hcy in PCOS. Material and methods. One hundred and twenty-nine women aged 20–28 years were examined: the main group — 98 patients with PCOS, the control group — 31 healthy women. The serum content of Hcy was evaluated and a molecular genetic study was conducted to identify the MTHFR, MTR, and MTRR genes. Results. Polymorphic variants of genes involved in folate metabolism were found in both patients with PCOS and in healthy women. However, serum concentration of Hcy was significantly higher in PCOS. Analysis of the MTHFR C677T polymorphism gene showed that the presence of the mutant T allele was associated with an increased Hcy level (12.9 ± 0.2 μmol/l) and the risk of PCOS (odds ratio (OR) = 1.19; 95% confidence interval (CI) 0.52–2.71). In the presence of two T alleles, the level of Hcy (14.6 ± 0.3 µmol/L) and the risk of developing PCOS (OR = 7.69; 95% CI 0.98–59.87) increased even further compared to the functionally “normal” C677C genotype. There was also an association between the MTHFR gene polymorphism at locus 1298 and PCOS whose strength depended on the number of pathological C alleles and was mediated by Hcy content, although this mutation was accompanied by a less significant increase in the level of Hcy than the mutation at locus 677. Compared to carriers of the homozygous A1298A genotype, the risk of developing PCOS was 5.7 times higher in patients with one C allele, and 7.3 times higher in the presence of two C alleles. The MTRR A66A and A66G genotypes were associated with a significant increase in the level of Hcy compared to that of the control group and were associated with an increased risk of PCOS. The mutant homozygous G66G genotype was more common in the control group and had no significant effect on Hcy concentration. It is not proved that the MTR gene is a candidate gene for the development of PCOS, and its polymorphic variants have a negative effect on the level of Hcy. The combination of MTHFR C677T and A1298C, MTHFR C677T and MTR A2756G, MTR A2756G and MTRR A66G gene mutations are associated with a greater increase in Hcy and the risk of developing PCOS compared to any individual monomutation. Conclusions. The MTHFR gene polymorphism and the synergistic effect of the MTHFR, MTR, MTRR gene mutations can be important genetic determinants for homocysteine levels and the risk of PCOS.